Challenges Associated With the Civilian Reintegration of Soldiers With Chronic PTSD: A New Approach Integrating Psychological Resources and Values in Action Reappropriation - Belrose, Célia; Duffaud, Anais M.; Dutheil, Frédéric; Trichereau, Julie; Trousselard, Marion (Frontiers in Psychiatry, 2019)
Background: In light of the psychological changes in an individual suffering from chronic Posttraumatic Stress Disorder (PTSD), questions are being raised in order to understand and facilitate recovery and a return to work. This is particularly challenging for soldiers suffering from chronic PTSD, who are often young individuals suffering from moral conflicts. A French military rehabilitation program proposes the broadening of the relationships between recovery and reintegration by incorporating approaches from the field of positive psychology for soldiers with chronic PTSD. The aim of the study was to evaluate (i) the psychological resources which remain sustainable for these trauma exposed soldiers according to their PTSD symptoms, (ii) the dynamics of resource reappropriation after the military rehabilitation program, which focuses on values in action (VIA) as character strengths, and (iii) how these resources and their reappropriation facilitate civilian professional reintegration. Method: We conducted a prospective study with 56 trauma exposed soldiers with a clinical diagnosis of chronic PTSD. PTSD severity and psychological resources (optimism, mindfulness, well-being, motivation, self-esteem, and VIA) were assessed before and after the rehabilitation program. After the identification of resource profiles, we analyzed the impact of the program on resource levels and successful reintegration into a civilian job. Results: 3 profiles were identified based on the psychological resources of the soldiers. Profiles 1, 2, and 3 differed in terms of clinical severity (PCL5). Profile 1 exhibited both the highest level of resources and the lowest clinical severity of PTSD but did not modify its resources after the intervention program when compared to profile 3. Profile 3 was characterized by the lowest level of resources, the highest clinical severity of PTSD and the highest reappropriation in all VIAs. This profile was associated with the highest rate of reintegration success 1 year after the intervention. Conclusions: This paper aims to broaden the relationship between recovery and reintegration by incorporating approaches from the field of positive psychology for soldiers with PTSD. VIA appears to be an important factor for reintegration. Our results highlight the importance of taking into account the existing needs of the patient and the optimization of the modalities of individual, collective, and institutional rehabilitation for patients suffering from PTSD in order to better understand the dynamics of the recovery process of a chronically afflicted individual.